Cytohesin‐2 phosphorylation by protein kinase C relieves the constitutive suppression of platelet dense granule secretion by ADP‐ribosylation factor 6. (May 2014) - van den Bosch, M. T. J.; Poole, A. W.; Hers, I.
Summary Background Protein kinase C (PKC) is a major regulator of platelet function and secretion. The underlying molecular pathway from PKC to secretion, however, is poorly understood. By a proteomics screen we identified the guanine nucleotide exchange factor cytohesin‐2 as a candidate PKC substrate. Objectives We aimed to validate cytohesin‐2 as a PKC substrate in platelets and to determine its role in granule secretion and other platelet responses. Methods and results Immunoprecipitation was performed with a phosphoserine PKC substrate antibody followed by mass spectrometry, leading to the identification of cytohesin‐2. By western blotting we showed that different agonists induced cytohesin‐2 phosphorylation by PKC. Protein function was investigated using a pharmacological approach. The cytohesin inhibitor SecinH3 significantly enhanced platelet dense granule secretion and aggregation, as measured by lumi‐aggregometry. Flow cytometry data indicate that α‐granule release and integrin αIIbβ3 activation were not affected by cytohesin‐2 inhibition. Lysosome secretion was assessed by a colorimetric assay and was also unchanged. As shown by western blotting, ARF6 interacted with cytohesin‐2 and was present in an active GTP‐bound form under basal conditions. Upon platelet stimulation, this interaction was largely lost and ARF6 activation decreased, both of which could be rescued by PKC inhibition. Conclusions Cytohesin‐2 constitutively suppresses platelet dense granule secretion and aggregation by keeping ARF6 in a GTP‐bound state. PKC‐mediated phosphorylation of cytohesin‐2 relieves this inhibitory effect, thereby promoting platelet secretion and aggregation.